The Effect of Audit Committee, Profitability, Company Size, and Leverage on Audit Report Lag - Wrensiska, Dwi; Indrati, Menik (Journal Research of Social Science, Economics, and Management, 2025)
This study examines the factors influencing audit report lag in the transportation and logistics sector, addressing the persistent problem of delayed financial reporting that undermines market transparency and investor confidence. The research problem stems from the significant number of companies listed on the Indonesia Stock Exchange (IDX) that consistently exceed the 90-day regulatory deadline for submitting audited financial statements, with audit report delays potentially causing administrative fines, declining investor confidence, and capital market volatility. The objectives are to analyze the effects of audit committee characteristics, profitability, company size, and leverage on audit report lag in transportation and logistics companies. Using a quantitative approach with panel data regression based on the Fixed Effect Model (FEM), this study examines 24 companies listed on the IDX during 2022–2024, resulting in 72 observations through purposive sampling. The results of the study show that while larger businesses and more extensive audit committee structures speed up the audit process, audit report delay is negatively and significantly impacted by audit committee characteristics and firm size. Meanwhile, audit report delays have not been significantly impacted by profitability or debt. The results of the study have managerial implications for improving the performance of audit committees and making the best use of available resources to reduce audit report delays and improve the openness and dependability of financial data.